THEORETICAL ASPECTS OF THE FORMATION OF LAW ENFORCEMENT OFFICER'S PROFESSIONAL CULTURE - Myroslav Kushniruk; Andrii Melnyk (Vasyl Stefanyk Precarpathian National University, 2018)
The article deals with various scientific approaches to the definition of the structure essence of the law enforcement officer's professional culture. It is substantiated the necessity of forming a professional culture in connection with the reformation of the law-enforcement system of Ukraine in accordance with the world standards of advanced countries of the world. It is analyzed the works of domestic and foreign scientists who in their researches emphasized the importance of forming a professional culture of the law enforcement officer. Different scientific approaches to the definition of the essence of the structure of the professional culture of the law enforcement officer are analyzed. The structure of professional culture is investigated and the general conclusion is drawn that it has two main components: the first component characterizes the way of interaction of the subject with the instruments and the subject of activity, as well as the degree of his readiness for a specific type of activity. It includes such elements as professional interest, knowledge, skills and abilities, including the style of professional thinking. The second component is an integral characteristic of consciousness and self-awareness of the subject of professional culture, moral-ideological and aesthetic preconditions of activity.The professional culture of the future law-enforcement officer is considered at different levels of development. So at the initial level the degree of formation of the system of professional knowledge and views is not yet sufficiently wide, professional abilities are in the stage of formation. Attitude to work can be narrowed down utilitarian factors. The higher the level of knowledge and skills, the wider the experience, the more likely that the law enforcement officer in his professional activities can reach certain heights. For a higher level, there is a wide professional outlook, and a large amount of professional knowledge, interests and skills, and a creative understanding of the production situation as a problem problem, and the ability to solve it productively, in an original, efficient way. It was presented the main functions of professional culture and stages of its formation in the process of professional training of future law enforcement officers in higher educational institutions of Ukraine with specific learning conditions. Key words: law enforcement officer's professional culture, development of personality, personal culture, components of professional culture.